Common mistakes in combating illegal crypto mining - Shahul Ikram, Nur Adlin Hanisah; Zul Kepli, Mohd Yazid (Fakulti Undang-undang UKM, 2021)
The explosive rise of cryptocurrencies price have escalated interest on this class of digital asset, resulting in an increased number of illegal crypto mining. The Cambridge Center for Alternative Finance (CCAF) estimates that Malaysia is responsible for around 3.5% of all world’s bitcoin miners, placing Malaysia in the top ten destinations in the world for crypto mining. There has been consistent increase in reported cases of police raids on illegal premises committing electricity theft, and other unlicensed activities which causes million ringgits losses to the government and to Malaysia’s energy provider like Tenaga Nasional Berhad (TNB). The crypto crackdowns by Malaysian authorities on illegal miners that actively siphoned electricity have made regular headlines in Malaysian newspapers. Despite the series of crackdowns, the number of person prosecuted have been very low, unrealistic and failed to prevent others from committing these crimes. This study aims to highlight the legal and regulatory defects in the current framework and the common mistakes in combating illegal crypto mining. A series of possible solutions for these costly problems is also included.